2020
DOI: 10.21608/ajar.2020.149411
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the volatile compounds and sensory characteristics of some locally produced potato chips

Abstract: This study was carried out to evaluate the volatile compounds in the headspace of two types of fried potato chips (A and B), flavoured with salt only. The impact of seasoning addition (tomato, onion and cheese) that are highly preferred by consumers on the flavour quality of these two potato snacks was investigated. A comparative study concerning fat contents, headspace volatiles and sensory characteristics was carried out between the two brand types of tested potato chips. The results indicated that the lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…This observation was in tandem with the pyrazine's concentration in the different chips (Table 3). Previous studies on the aroma profile of potato chips also reported that pyrazines were responsible for the nutty, roasty, and chocolate aroma in potato chips (Mohamed et al, 2020;Xu et al, 2021) and corn tortilla chips (El-Shayeb et al, 2018), respectively. Overall, the sensory evaluation of the deep-fried chips was characterised by deep-fried, fatty, nutty, roasty, chocolate-like, and malty nuances (Figure 3).…”
Section: Sensory Analysis Of Fried Arrowhead Corm Chipsmentioning
confidence: 93%
“…This observation was in tandem with the pyrazine's concentration in the different chips (Table 3). Previous studies on the aroma profile of potato chips also reported that pyrazines were responsible for the nutty, roasty, and chocolate aroma in potato chips (Mohamed et al, 2020;Xu et al, 2021) and corn tortilla chips (El-Shayeb et al, 2018), respectively. Overall, the sensory evaluation of the deep-fried chips was characterised by deep-fried, fatty, nutty, roasty, chocolate-like, and malty nuances (Figure 3).…”
Section: Sensory Analysis Of Fried Arrowhead Corm Chipsmentioning
confidence: 93%